The Environmental Impact of a Pro-Environment International Governmental Meeting: Evidence from Italy - Vincenzo Alfano; Giuseppe Lucio Gaeta (Center for Economic Studies and ifo Institute (CESifo), 2022)
This note contributes to the literature on the air pollution consequences determined by hosting mega-events. An econometric analysis is provided to document the increase in air pollution observed in Naples (Italy) during the G20 Ministerial meeting on the Environment, Climate, and Energy carried out in July 2021. Such evidence contributes to understanding the potential costs of mega-events in a metropolitan area with low air quality and high private car density. Findings suggest that mega-events cause a decrease in air quality. Therefore, we suggest to organize mega-event outside cities. The media coverage would not be lowered by this policy, and on the contrary it could be a useful occasion to re-discover inner, less urbanized area.
Keywords: Q51; Q53; 330; G20 meeting; mega-event; pollution